Factors Affecting the Data Warehouse Implementation Success: an Exploratory Study - Alsqour, Moh'd; Owoc, Mieczysław L. (Czynniki wpływające na powodzenie wdrożenia hurtowni danych: studium badawcze, 2010)
The ultimate purpose of this paper is to investigate the adoption and/or implementation of Data Warehouse (DW) technology among firms in Poland. The factors which are expected to influence the mentioned processes were derived from previous studies in similar research areas. In this study a model of data warehousing implementation success was formulated based on an extensive literature review, previous studies, and own experience. This is initial investigation, therefore the results and findings will be published after collecting and analyzing the data in the authors' next separate supplementary paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 11-21
Keywords: data warehouse implementation; literature review